Associations between workplace factors and carpal tunnel syndrome: A multi‐site cross sectional study. Issue 5 (16th March 2015) - Fan, Z. Joyce; Harris‐Adamson, Carisa; Gerr, Fred; Eisen, Ellen A.; Hegmann, Kurt T.; Silverstein, Barbara; Evanoff, Bradley; Dale, Ann Marie; Thiese, Matthew S.; Garg, Arun; Kapellusch, Jay; Burt, Susan; et al.
<x xml:space="preserve">Abstract</x> Background Few large epidemiologic studies have used rigorous case criteria, individual‐level exposure measurements, and appropriate control for confounders to examine associations between workplace psychosocial and biomechanical factors and carpal tunnel syndrome (CTS). Methods Pooling data from five independent research studies, we assessed associations between prevalent CTS and personal, work psychosocial, and biomechanical factors while adjusting for confounders using multivariable logistic regression. Results Prevalent CTS was associated with personal factors of older age, obesity, female sex, medical conditions, previous distal upper extremity disorders, workplace measures of peak forceful hand activity, a composite measure of force and repetition (ACGIH Threshold Limit Value for Hand Activity Level), and hand vibration. Conclusions In this cross‐sectional analysis of production and service workers, CTS prevalence was associated with workplace and biomechanical factors. The findings were similar to those from a prospective analysis of the same cohort with differences that may be due to recall bias and other factors. Am. J. Ind. Med. 58:509–518, 2015. © 2015 Wiley Periodicals, Inc.